1987
DOI: 10.1016/0044-8486(87)90061-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in steroid metabolism in the male reproductive organ-system of the African catfish, Clarias gariepinus

Abstract: In testes, the capacity to form progestins, androgens, especially ll-oxygenated ones, and steroid glucuronides increased enormously in the periods of full spermatogenesis and breediig, with 5#?-pregnane-3a,17a,20a-triol and 5fi-pregnane-3a,17t-diol-20-one glucuronide as the main polar products. In the same periods, seminal vesicles are able to form ll-oxygenated androgens from[ 3H] -androstenedione and show an increased capacity to form testosterone. Their ability to produce testosterone glucuronide is strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…SP-Androstane-3@,17P-diol was detectable only as free steroid, while Sp-dihydrostestosterone and SP-androstane-3or, 11 P-diol-17-one could no be demonstrated at all, although these steroids were present after in vitro incubations of seminal vesicle tissue Schoonen et al, 1987b;Resink et al, 1987a).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…SP-Androstane-3@,17P-diol was detectable only as free steroid, while Sp-dihydrostestosterone and SP-androstane-3or, 11 P-diol-17-one could no be demonstrated at all, although these steroids were present after in vitro incubations of seminal vesicle tissue Schoonen et al, 1987b;Resink et al, 1987a).…”
Section: Discussionmentioning
confidence: 94%
“…The results of in vitro incubation studies indicate that the seminal vesicle is capable of synthesizing various steroids and at least six different, steroid glucuronides ( Fig. 9) (Schoonen and, Laml bert, 1986;Schoonen et al, 198%, 6;. Resink et al, 1987a).…”
mentioning
confidence: 99%
“…Seminal vesicle fluid elicited a dose-dependent attraction when added to the aquarium water of ovulated females. On the other hand, a high dose induced an avoidance reaction (Resink et al, 1987 a).…”
Section: Steroids Frorn Gorzadal Origin With Pheromorzui Propertiesmentioning
confidence: 99%
“…Comparing the capacity of ovarian tissue to metabolise prcgnenolone and androstenedione, Schoonen et al (1987 d) found that during the breeding period before as well immediately after spawning the ovaries can synthesis estradiol-1713, estrone and sevcral progestines and androgens, including 5[j-reduced C2 1 -and C19-steroids. Testosterone and most of the 50-reduced products were also identified in a conjugatcd form as steroid glucuronides.…”
Section: Steroids Frorn Gorzadal Origin With Pheromorzui Propertiesmentioning
confidence: 99%
“…These conjugates may be involved in reproduction, since the capacity to form them in feral African catfish is markedly enhanced during the breeding season, both in testes and in the seminal vesicle (Resink et al, 1987b); an additional increase is observed in the latter organ during actual spawning (Resink et al, 1987a). The latter phenomenon is accompanied by a rise of circulating gonadotropin.…”
mentioning
confidence: 93%